Optimalisasi Pembelajaran Melalui Aplikasi Interaktif di Pondok Pesantren XYZ Polewali Mandar - KH, Musliadi; Ismail, Asriyani; Hasnining, Ayu (Journal of Digital Ecosystem for Natural Sustainability, 2024)
The low ability of humans to absorb material from what they read, hear, and see, and the combination of seeing and hearing increases the absorption of material by up to 50%. This situation shows the need for efforts to improve student learning outcomes. One solution proposed to overcome this problem is using interactive animation in learning. This research aims to analyze, design, and implement interactive learning applications at the XYZ Islamic Boarding School in Polewali Mandar Regency. Then examine how information and communication technology can be used to overcome the problem of lack of teaching aids and make the learning process more interesting and effective. Research methods include needs analysis, application design, development, and implementation evaluation. This study also refers to the successful use of multimedia technology in education, such as multimedia-based Al-Quran learning applications and interactive educational games that increase student learning motivation. The research results in the form of interactive learning applications can improve the quality of learning in Islamic boarding schools, make the teaching and learning process more fun and interactive, and help students absorb material more effectively.